Gestión contable y tributaria y la rentabilidad - Marcillo Vera, Magaly Esther (2024)
The purpose of this research work called Accounting and tax management and profitability is to analyze the incidence of accounting and tax management in small companies, taking into consideration two businesses in the Paján Canton. In the references there are various techniques that will be used in the present investigation, such as the interview addressed to experts in the accounting area and the survey applied to small companies in the Paján Canton, with the aim of learning more about the subject of accounting control. and tax that businesses must have to obtain greater profitability; considering the type of mixed approach, since it has a qualitative and quantitative approach..............